Body weight perception, disordered weight control behaviors, and depressive symptoms among Korean adults: The Korea National Health and Nutrition Examination Survey 2014. - Yongjoo Kim; S Bryn Austin; S V Subramanian; Ichiro Kawachi (PLoS ONE)
Background/ purpose Despite emerging evidence suggesting harmful influences of accurate weight perception on psychological health among individuals with obesity, little is known about the association in Asian populations. The aim of this study was investigate the association between body weight perception and depressive symptoms among Korean adults, and potential differential associations across gender. Methods We used data from the sixth Korea National Health and Nutrition Examination Survey in 2014, comprising 3,318 female (n = 1,876) and male (n = 1,442) participants, aged 19-65 years, with no history of depression and a body-mass index (BMI)> = 18.5kg/m2. Depressive symptoms were measured by the Patient Health Questionnaire-9 Korean version. Weight perception patterns were categorized by comparing self-perceived and objectively measured weight status. Gender-stratified four-level multilevel linear models adjusted for age, BMI, menopause, education, income, marital status, urbanicity, chronic conditions, exercise, smoking, and alcohol use. Subgroup analyses were performed across BMI category. Results Among women with obesity, those who underperceived their weight status reported fewer depressive symptoms compared to those who accurately perceived their weight status (β = -1.25, p<0.05). Among women with normal weight, those who overperceived their weight status reported more depressive symptoms compared to those who accurately perceived their weight status (β = 1.00, p<0.05). The same associations were not found in men. Conclusion Awareness-oriented strategies for obesity prevention and weight management focused on providing information on weight status may need to consider unintended consequences of accurate weight perception on mental health among individuals with obesity, particularly among women.